Lived experiences of female second-cycle students with abnormal menstrual cycle in a selected municipality of Ghana: A phenomenological qualitative study - Cate Degbor; Emmanuel Manu (PLoS ONE, 2026)
Background Menstruation can be accompanied by stressful experiences and one such experience is the abnormal menstrual cycle, which could include menstrual irregularity and painful menstruation. Menstrual irregularity is defined as deviations in cycle length, frequency, or flow and can occur at any age, but it is most common among young women, often school-going children. Lack of understanding of abnormal menstruation often exposes young girls to adverse health outcomes. There is limited qualitative evidence on the lived experiences, beliefs, and coping strategies of secondary-school girls experiencing irregular menstrual cycles, particularly in rural settings. Objective We explored the lived experiences of female second-cycle students with irregular menstrual cycles in a selected district in Ghana to inform policy on menstrual health education. Methods We employed a phenomenological qualitative research approach to purposely interview 28 students using an in-depth interview guide. A thematic approach was used to analyze the data using ATLAS.ti v 7.5. Result For lived experiences, patterns of menstrual flow characterized by inconsistent menstrual blood flow were a major reason they considered their menstrual cycle irregular. The challenges faced were physical and emotional. The students have personal beliefs that an irregular menstrual cycle is a sickness and a sign of infertility, which is caused by food and diet (unhealthy diet and sugary foods). The main coping mechanisms adopted were resting, hot water therapy, and medication and support from friends and family. Conclusion The study provides an in-depth understanding of irregular menstrual cycles and their significant impact on the well-being of secondary school girls.